2022
DOI: 10.9734/ijpss/2022/v34i242671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Farmyard Manure (FYM) and Zinc Fertilizer Application on Yield Parameters of Common Wheat (Triticum aestivum L.) Grown on Sandy-clay Loam of Borno State, Nigeria

Abstract: A Screen House experiment was carried out in University of Maiduguri to study the effects of Farmyard Manure (FYM) and Zinc fertilizer rates on wheat (Triticum aestivum L.) grain yield, 1000 grain weight, total dry matter weigh and HI on Sandy Clay-loam soil with location; Latitude (11.923100 ON and 11.919042 ON) and Longitude (13.228927 OE and 13.221758 OE) of Jere Local Government Area, Borno state, Nigeria. The study was set out in CRD with 3 replications. Composite 10 kg soil was weighed into 36 pots and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…This aligned with a previous study by Debbarma et al (2020) [6] and Jackson et al (2019) [13] , the use of the complete recommended NPK plus VC @ 2 tonnes per hectare and full recommended dose of NPK plus VC @ 1 tonne per hectare and Zn @ 5 kilograms per hectare had a positive influence as they recorded maximum harvest index (46.322 and 45.01%, respectively) followed by 100% NPK with harvest index of 44.92%. it was aligned with previous studies by Zubairu et al (2022) [29] have demonstrated significant impacts of different nutrient sources on the harvest index. was registered in (T6) 100% NPK in conjunction with VC at 2 tonnes per hectare, which was due to higher quantities of vermicompost applied.…”
Section: Harvest Indexsupporting
confidence: 92%
“…This aligned with a previous study by Debbarma et al (2020) [6] and Jackson et al (2019) [13] , the use of the complete recommended NPK plus VC @ 2 tonnes per hectare and full recommended dose of NPK plus VC @ 1 tonne per hectare and Zn @ 5 kilograms per hectare had a positive influence as they recorded maximum harvest index (46.322 and 45.01%, respectively) followed by 100% NPK with harvest index of 44.92%. it was aligned with previous studies by Zubairu et al (2022) [29] have demonstrated significant impacts of different nutrient sources on the harvest index. was registered in (T6) 100% NPK in conjunction with VC at 2 tonnes per hectare, which was due to higher quantities of vermicompost applied.…”
Section: Harvest Indexsupporting
confidence: 92%